RISK FACTOR RELATED TO PRIMARY POST PARTUM HEMORRHAGE AT RADEN MATTAHER REGIONAL HOSPITAL JAMBI PROVINCE IN 2019 - Rosmaria Rosmaria; Yuni Susanti (Poltekkes Kemenkes Jambi, 2019)
Background: Primary postpartum hemorrhage that occurs within the first 24 hours is the highest cause of maternal mortality in Indonesia. This study aimed to determine the risk factors associated with the incidence of primary postpartum hemorrhage at Raden Mattaher Regional Hospital Jambi Province in 2019. Methods: This was an analytic survey with observational method using a case control approach. A total of 48 of primary post partum hemorrhage case were included as the case samples using total sampling technique and 48 control samples were recruited using purposive sampling with a ratio of 1: 1. Data collection was done by documentation followed by univariate and bivariate data analysis. Results: The results of the univariate study showed that some of the respondents’ age and parity status were at risk of anemia. Bivariate results showed that age (p-value = 0.002 and OR = 4.109), parity (p-value = 0.000 and OR = 7.400)and anemia (p- value = 0,000 and OR = 14,224) were associated with the incidence of primary postpartum hemorrhage.. Conclusion: Age, parity and anemia was a significant factors acosiated with the incidence of primary postpartum hemorrhage at Raden Mattaher Regional Hospital Jambi Province